Mergers Trigger Significant Shifts in Company Stock Performance - Junita Pratiwi; Saparuddin Siregar; Suhairi Suhairi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Mergers are strategic business activities aimed at enhancing competitiveness, operational efficiency, and shareholder value through the consolidation of two companies. Specific Background: In the Indonesian capital market, corporate mergers among publicly listed firms are becoming increasingly relevant as investors seek signals that predict future financial performance. Knowledge Gap: Despite numerous merger activities, empirical evidence on the financial impact of mergers in Indonesia remains limited and inconclusive. Aims: This study investigates the financial performance of eight public companies listed on the Indonesia Stock Exchange following mergers, to determine if significant changes occur. Results: Using a quantitative approach with purposive sampling and secondary data from IDX, IDN Financial, and Investing websites, financial ratios before and after the merger were compared through a T-test. The analysis revealed statistically significant differences in all observed financial ratios post-merger.Novelty: The study offers contextual evidence on how mergers in emerging markets like Indonesia can reshape financial performance, supporting investment decisions based on merger outcomes. Implications: These findings contribute to a better understanding for market investors, indicating that mergers may serve as reliable indicators for potential profitability and improved financial health in the post-merger period. Highlights: Mergers significantly affect company financial ratios. T-test reveals post-merger performance shifts. Results guide investors in stock decision-making. Keywords: Merger Impact, Financial Performance, Indonesia Stock Exchange, Quantitative Analysis, Investor Strategy